2011
DOI: 10.1002/hed.21700
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prophylactic percutaneous endoscopic gastrostomy on malnutrition and quality of life in patients with head and neck cancer — a randomized study

Abstract: Prophylactic PEG was associated with significantly earlier start and longer use of enteral nutrition, fewer malnourished patients over time, and improved HRQOL at 6 months posttreatment start.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
227
9
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(249 citation statements)
references
References 38 publications
7
227
9
3
Order By: Relevance
“…Recently, a randomized controlled trial showed evidence for prophylactic PEG placement in the prevention of malnutrition and improved quality of life in patients with advanced head and neck cancer (12). Moreover, Raykher reported that PEG feeding allowed CRT to continue without interruption in 93% of patients with head and neck cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a randomized controlled trial showed evidence for prophylactic PEG placement in the prevention of malnutrition and improved quality of life in patients with advanced head and neck cancer (12). Moreover, Raykher reported that PEG feeding allowed CRT to continue without interruption in 93% of patients with head and neck cancer (13).…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma is a subset of cancer in this area, with differences in natural history and treatment regimens were blended in with the studies. The number of nasopharyngeal carcinoma patients in these studies were 23%, 15% and 1.5% in Chen et al (2009) Mercuri et al (2010 and Silander et al (2011)'s studies, respectively. These results may not fit nasopharyngeal carcinoma because the chemotherapy regimen and target volume of radiation are different.…”
Section: Comparison Of Treatment Compliance and Nutritional Outcomes mentioning
confidence: 79%
“…They found 4.9 and 11.0% of weight loss from baseline in PPEG group and non-PPEG group (Mercuri et al, 2009). But Silander et al (2011) conducted a randomised control trial to evaluate the effect of PPEG on malnutrition and quality of life. They included 134 head and neck cancers, mainly oropharynx and oral cavity cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences in BMI at six months, but the proPEG group had a higher QOL for some domains at some time points. The second study (neutral quality) had no difference in weight loss outcomes, treatment delays, unplanned admissions or survival between groups, but the proPEG group had better QOL at six months for a number of domains, and less swallow problems at one year (Silander et al, 2012). These two studies both provide level II evidence that the prophylactic approach does not improve clinical or nutrition outcomes (although weight change was only monitored from six months post-treatment) but can improve some aspects of QOL compared to the reactive approach, with no impact on long-term swallow.…”
Section: Tube Feeding: Optimal Type and Timingmentioning
confidence: 90%